2020
DOI: 10.1136/bmjspcare-2020-002331
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related bloodstream infections in palliative care patients receiving parenteral nutrition by medical home care

Abstract: BackgroundCatheter-related bloodstream infections (CRBSIs) constitute a major complication associated with the use of central venous lines (CVL). The aim of this study was to investigate the incidence proportion and risk factors of CRSBI in palliative care patients with CVL receiving home parenteral nutrition (HPN).MethodsMedical records from patients admitted to a medical home care unit in stockholm, Sweden, during 2017 were reviewed (n=1022) and 454 palliative care patients with a CVL were identified. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Thirty-three articles were excluded during the first stage of screening, including seven review articles or guidelines without descriptions of any patient data, twelve articles for non-palliative intent, four articles with peripheral catheters and ten articles without details of CVAD-related complications. After screening the abstracts, eight publications were chosen to proceed with full-text review and two papers were excluded due to incomplete data retrieval [17,18]. A paper studying PORTs was excluded due to the administration of chemotherapy in a palliative care setting [19].…”
Section: Search Strategy Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three articles were excluded during the first stage of screening, including seven review articles or guidelines without descriptions of any patient data, twelve articles for non-palliative intent, four articles with peripheral catheters and ten articles without details of CVAD-related complications. After screening the abstracts, eight publications were chosen to proceed with full-text review and two papers were excluded due to incomplete data retrieval [17,18]. A paper studying PORTs was excluded due to the administration of chemotherapy in a palliative care setting [19].…”
Section: Search Strategy Resultsmentioning
confidence: 99%
“…chosen to proceed with full-text review and two papers were excluded due to incomplete data retrieval [17,18]. A paper studying PORTs was excluded due to the administration of chemotherapy in a palliative care se ing [19].…”
Section: Search Strategy Resultsmentioning
confidence: 99%
“…According to the literature [19] , PN's use appears to be a risk factor for the onset of CRBSI. It has been reported [20][21][22] that PN can increase the risk of CRBSI by three to ten times. Our study demonstrated that the duration of PN increased one day, the risk of fungal colonization in PICC tips was increased by 28%.…”
Section: Discussionmentioning
confidence: 99%